Literature Review: The Relationship Between The Incidence Of Infection And Length Of Stay In Burn Patients - Siti Aisyah Karina HB; Sri Vitayani; Syakir (International Medical Journal Corp. Ltd, 2025)
Burn injuries are a global health issue that cause high morbidity and mortality, particularly in low- to middle-income countries such as Indonesia. Infection is the most common complication that prolongs hospitalization and increases the risk of death in burn patients. The aim of this study is to review the relationship between infection incidence and the length of hospital stay in burn patients based on national and international literature. Based on the review of 10 articles, it was found that infections caused by resistant pathogenic bacteria such as Pseudomonas aeruginosa, Acinetobacter baumannii, and Staphylococcus aureus significantly extend the duration of treatment. Other risk factors, including the extent of the burn, delayed treatment, and immune response, also affect the length of hospitalization. Proper and early management—including wound care, antimicrobial therapy, and community education—is crucial for accelerating the healing